The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.tjog.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative measurement of maternal abdominal circumference relates the initial sensory block level of spinal anesthesia for cesarean section: An observational study

Abstract: Parturients with greater abdominal circumference value have a higher level of sensory blockade at 5 minutes after spinal anesthesia. Abdominal circumference cannot predict the maximum sensory blockade level and the incidence of hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…[ 2 ] Similar finding was reported by Kuok et al ., who found that at 5 th min, increased abdominal circumference lead to higher level of sensory blockade. [ 5 ] This finding was also corroborated by Baysal et al ., who found large abdominal circumference shortened the time taken for sensory block to reach T4. [ 14 ] Effect of intra-abdominal pressure on sensory blockade has been studied with negative results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[ 2 ] Similar finding was reported by Kuok et al ., who found that at 5 th min, increased abdominal circumference lead to higher level of sensory blockade. [ 5 ] This finding was also corroborated by Baysal et al ., who found large abdominal circumference shortened the time taken for sensory block to reach T4. [ 14 ] Effect of intra-abdominal pressure on sensory blockade has been studied with negative results.…”
Section: Discussionsupporting
confidence: 83%
“…Hence, various parturient factors such as height, weight, body mass index, body surface area, truncal length, symphysis-fundal height, abdominal circumference, and weight gain during pregnancy have been studied to know their effects on the level of sensory blockade after spinal anesthesia which have led to inconclusive or negative results. [ 4 5 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…We measured the level of anesthesia only after completing the spinal anesthesia and just before the surgical incision. In a previous study, Kuok et al found a correlation between the AC and sensory block level (right side ρ = 0.43, p =0.005; left side ρ = 0.46, p =0.003) [ 7 ]. However, those researchers did not find a correlation between the incidence of hypotension, defined as ≥30% decrease of blood pressure from baseline, and AC.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is impractical to measure abdominal pressure and attempts to do so can increase the risk of infection. Previous studies have demonstrated associations between larger abdominal circumference (AC) and higher abdominal pressure [ 5 ] and level of sensory block [ 6 , 7 ]. Therefore, it is rational to use AC as a surrogate for abdominal pressure in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Greene 4 has described 25 factors that affect the spread of spinal anaesthesia but in clinical practice it is hard to isolate one factor and quantify its effect on the spread of spinal anaesthesia from the others. There is a great interest on defining the determinants of spinal anaesthesia spread in recent studies (5)(6)(7)(8)(9). Measures that are practically obtainable and have a predictive value on spinal anaesthesia spread will help the clinicians to predict the spread of spinal anaesthesia for individual patients.…”
Section: Introductionmentioning
confidence: 99%